Adaptation and Some Quality Parameters of Cool Season Turfgrass Species in Samsun Conditions - Ayan, İlknur and Arslan, Sedat and Acar, Zeki (Turkish Journal of Agriculture - Food Science and Technology, 2020)
The aim of this study is to determine adaptation and quality parameters of some cool season turfgrass cultivars and species, In the scope of this study, leaf form, variation of leaf colour according to the seasons, tiller number, thinning ratio, weed ratio and general appearance of the species were determined. The experiment was established according to confounding design with four replications in Samsun Conditions at November, 2010. According to 1000 seed weight and characteristics of the plants seeding ratios were determined as pure and viable seed as follows; Lolium perenne 40 g m-2, Festuca rubra var. rubra and Festuca rubra var. commutata 30 g m-2, Festuca arundinacea 40 g m-2, Poa pratensis 20 g m-2, Festuca rubra trichophylla 30 g m-2, Agrostis stolonifera and Agrostis tenuis 5 g m-2, Festuca ovina 25 g m-2. According to the results obtained from this study it was determined that species/cultivars have some superiority to each other because of their different morphological and physiological characteristics. When we consider weed competition, Lolium perenne and Festuca arundinaceae cultivars have to be added to the mixture in order to decrease weed competition. There was colour variation distinctively depending on the seasons for all species. But, compare to the others, cultivars of Agrostis sp. and Poa pratensis cultivars have the potential to keep leaf colour in different seasons. Leaf form and appearance of Festuca rubra, Poa trivialis and Festuca ovina are better than the others. In order to keep good conditions of turfgrass areas, especially after cutting in summer period, Poa pratensis and Poa trivialis should added in mixtures to get benefit their higher regenerating power.